Clinical approach to genetic testing in amyloid cardiomyopathy: from mechanism to effective therapies. (May 2021) - Alreshq, Rabah; Ruberg, Frederick L.
Abstract : Purpose of review: To highlight the evolving understanding of genetic variants, utility of genetic testing, and the selection of novel therapies for cardiac amyloidosis. Recent findings: The last decade has seen considerable progress in cardiac amyloidosis recognition given the advancement in cardiac imaging techniques and widespread availability of genetic testing. A significant shift in the understanding of a genetic basis for amyloidosis has led to the development of disease-modifying therapeutic strategies that improve survival. Summary: The systemic amyloidoses are disorders caused by extracellular deposition of misfolded amyloid fibrils in various organs. Immunoglobulin light-chain or transthyretin amyloidosis are the most common types associated with cardiac manifestations. Genetic testing plays a central role in the identification of genotypes that are associated with different clinical phenotypes and influence prognosis. Given the emergence of effective therapies, a systematic approach to the diagnosis of cardiac amyloidosis, with the elucidation of genotype when indicated, is essential to select the appropriate treatment.